Influence of Annealing on the Morphology of the Vacuum-free Coatings NbNх, NbNx : Si - V.N. Rogoz; A.P. Kuzmenko; O.V. Sobol’; A. Plyushchyk (Журнал нано- та електронної фізики)
The paper describes the features of niobium nitride coating changes with the addition of silicon and impurities without him. Samples were prepared by magnetron sputtering at a negative potential Us = − 40 V on silicon substrate, exposed to high temperatures: 800 °C without vacuum.